Frecast : message transmission model for ad hoc networks - 394003 Sakhinah Abu Bakar (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2004